Chronic intermittent hypoxia–hypercapnia blunts heart rate responses and alters neurotransmission to cardiac vagal neurons. (19th May 2014) - Dyavanapalli, Jhansi; Jameson, Heather; Dergacheva, Olga; Jain, Vivek; Alhusayyen, Mona; Mendelowitz, David
Abstract : Key points: Chronic intermittent hypoxia–hypercapnia (CIHH) in adult rats evoked hypertension and blunted the heart rate responses to acute hypoxia–hypercapnia (H–H). CIHH induced an increase in spontaneous inhibitory and decreased excitatory neurotransmission to cardiac vagal neurons. CIHH completely abolished acute H–H evoked inhibition of GABAergic while facilitating glycinergic neurotransmission to cardiac vagal neurons of nucleus ambiguus. These changes with CIHH inhibit cardiac vagal neurons to result in diminished cardioprotective vagal activity to the heart, characteristic of obstructive sleep apnoea. Abstract: Patients with obstructive sleep apnoea experience chronic intermittent hypoxia–hypercapnia (CIHH) during sleep that elicit sympathetic overactivity and diminished parasympathetic activity to the heart, leading to hypertension and depressed baroreflex sensitivity. The parasympathetic control of heart rate arises from pre‐motor cardiac vagal neurons (CVNs) located in nucleus ambiguus (NA) and dorsal motor nucleus of the vagus (DMNX). The mechanisms underlying diminished vagal control of heart rate were investigated by studying the changes in blood pressure, heart rate, and neurotransmission to CVNs evoked by acute hypoxia–hypercapnia (H–H) and CIHH. In vivo telemetry recordings of blood pressure and heart rate were obtained in adult rats during 4 weeks of CIHH exposure. Retrogradely labelled CVNs were identified in an in vitro brainstem slice preparation obtained from adult rats exposed either to air or CIHH for 4 weeks. Postsynaptic inhibitory or excitatory currents were recorded using whole cell voltage clamp techniques. Rats exposed to CIHH had increases in blood pressure, leading to hypertension, and blunted heart rate responses to acute H–H. CIHH induced an increase in GABAergic and glycinergic neurotransmission to CVNs in NA and DMNX, respectively; and a reduction in glutamatergic neurotransmission to CVNs in both nuclei. CIHH blunted the bradycardia evoked by acute H–H and abolished the acute H–H evoked inhibition of GABAergic transmission while enhancing glycinergic neurotransmission to CVNs in NA. These changes with CIHH inhibit CVNs and vagal outflow to the heart, both in acute and chronic exposures to H–H, resulting in diminished levels of cardioprotective parasympathetic activity to the heart as seen in OSA patients.